Orbital Apex Syndrome With Encephalitis: A Rare and Serious Complication of Herpes Zoster Ophthalmicus (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2021)
Introduction: Herpes zoster reactivation is more common in the elderly population. Although ocular complications are seen in 20-70% of patients with herpes zoster ophthalmicus, orbital apex syndrome is a rare case. Encephalitis is also a rare neurologic complication of HZO. Purpose: To report a Herpes Zoster Ophthalmicus (HZO)case with rare neurologic complication that ophthalmologist should be aware of. Case Presentation: A 68-year-old man had a chief complaint of a sudden blurred vision in right eye two days before admission, followed by rash and pain on the right upper eyelid and forehead. Visual acuity was hand movement on the right eye and 0.5 on the left eye. The patient had total ophthalmoplegia and total ptosis on his right eye, reverse relative afferent pupillary defect on his left eye and right peripheral facial nerve palsy. Optic discs were found to be normal on both eyes. The patient was diagnosed as orbital apex syndrome on his right eye associated HZO and right peripheral facial nerve palsy. The patient received oral acyclovir 800 mg five times/day and intravenous methylprednisolone 250 mg four times/day for three days. After four days of admission, the patient had a seizure and loss of his consciousness. The patient was consulted to neurology department and was given anticonvulsant therapy. The spinal tap revealed pleocytosis and increased protein. The patient was diagnosed as herpes zoster encephalitis. After one week, the patient regained full consciousness and his visual acuity was improved to 0.16 on the right eye. Color vision, visual field, and contrast sensitivity were also improved, ophthalmoplegia were partially resolved and peripheral facial nerve palsy was fully resolved. Conclusion: Herpes Zoster Ophthalmicus affect the central and peripheral nervous system at the same time and can be life-threatening with delayed diagnosis and treatment. It may be necessary to collaborate with the neurology department for every HZO case to minimize the life-threatening complications of HZO.